Influence of LRE (Ce, Y, and La) on microstructure and magnetic properties of (Nd0.8LRE0.2)–Fe–B hot-deformed magnets - Y. Milov (AIP Publishing LLC, 2021)
To develop low-cost, high-performance light rare earth element (LRE)-substituted Nd–Fe–B permanent magnets, we systematically studied the effect of substituting Nd with 20% light rare earth elements (LRE = Ce, Y, and La) on the hard magnetic properties of (Nd0.8LRE0.2)–Fe–B hot-deformed magnets. The (Nd0.8Ce0.2)2Fe14B magnet showed a coercivity of μ0Hc = 1.41 T, which is comparable to that of an LRE-free magnet. Y substitution was found to decrease μ0Hc and μ0Mr to 1.22 and 1.32 T, respectively, as was expected from the intrinsic properties of (Nd0.8Y0.2)2Fe14B. Unlike our expectation, the thermal stability of coercivity is not degraded by the Y substitution, demonstrating its potential for elevated temperature applications. With La substitution, coercivity is substantially degraded to 0.67 T because of the low intrinsic properties and the lack of the intergranular phase. The Y and Ce co-substituted (Nd0.8Ce0.1Y0.1)2Fe14B hot-deformed magnets showed better thermal stability of coercivity compared to the (Nd0.8Ce0.2)2Fe14B sample.